The Influence of Conventional and Digital Marketing Strategies on Commercial Vehicle Buying Interest in Increasing Commercial Vehicle Sales - Aminudin, Candra Aam; Purba , Yehezkiel Kevin Armando Prima; Usman , Osly (Manunggal Halim Jaya, 2025)
This study aims to analyse the impact of conventional and digital marketing strategies on consumer purchase intention in increasing commercial vehicle sales, with purchase intention serving as a mediating variable. A quantitative approach was employed using an explanatory research design. Data were collected through purposive sampling from 111 respondents, consisting of consumers who have either purchased or not yet purchased Hino brand commercial vehicles, including trucks and buses. The collected data were analysed using Structural Equation Modelling (SEM). The findings reveal that both conventional and digital marketing strategies have a positive and significant influence on consumer purchase intention, which in turn directly and indirectly contributes positively to sales performance. Furthermore, purchase intention acts as a significant mediating variable between marketing strategies and vehicle sales. The study concludes that purchase intention plays a crucial mediating role in the relationship between marketing strategies and the increase in commercial vehicle sales. These findings provide valuable insights for commercial vehicle dealers in selecting and implementing appropriate marketing strategies, particularly in leveraging both conventional and digital media to enhance consumer purchase intention and drive sales growth.